ENGLISH FUN WITH ARDUINO UNO UNTUK MENINGKATKAN KEMAMPUAN BAHASA INGGRIS ANAK USIA DINI - Ihtiari Prastyaningrum; Dian Ratnaningtyas Afifah; Rengganis Siwi Amumpuni (Institut Pendidikan Tapanuli Selatan, 2022)
The development of the era of globalization requires humans to master foreign languages, especially English. Because of this, learning English has been done from an early age. English learning is also carried out in PAUD institutions. Where English becomes local content. TKIT Nur Mujahidin as one of the PAUD institutions also applies the same thing. However, there are some difficulties related to media that can collaborate between audio and visual. Based on this, we tried to develop English Fun learning media. The method we use in this research is descriptive qualitative. Where our data obtained from observations and questionnaires. We also carry out the media validation process with media experts, material experts and teachers in kindergarten. The results of the study indicate that the English Fun media is quite valid and feasible to be used as a learning medium in PAUD. The results of the application of English Fun media showed that the children's mastery of the material had increased although it was not too significant.